Growing up in the Cis-Baikal region of Siberia, Russia : reconstructing childhood diet of Middle Holocene hunter-gatherers - Haas, Victoria M. van der (Archaeopress Archaeology, 2023)
This volume analyses the dietary life histories of prehistoric hunter-gatherers from six cemeteries in the Lake Baikal region of Siberia, Russia. The overarching goal was to better understand how they lived by examining what they ate, how they utilized the landscape, and how this changed over time.